The languages of East and Southeast Asia an introduction - Goddard, Cliff (Oxford University Press, 2005)
"This book introduces the linguistic diversity of East and Southeast Asia. It contains treatments of diverse areas including: word origins, cultural key words, tones and sounds, language families and typology, key syntactic structures, writing systems and communicative style" --Provided by publisher.